The Leasing Puzzle - ANG, JAMES; PETERSON, PAMELA P. (Journal of Finance, 1984)
ABSTRACT Prevailing theories in finance and economics suggest that leases and debt are substitutes; an increase in one should led to a compensating decrease in the other. In particular, there are three views on the magnitude of the substitution coefficient. Standard finance theory treats cash flows from lease obligations as equivalent to debt cash flows, thus describing the tradeoff between debt and leases as one‐to‐one. Others are willing to use a tradeoff of leases for debt which is less than, but close to, one. The rationale for a dollar of leases using less of debt capacity than a dollar of debt obligation is based upon the differences in the terms and nature of lease and debt contracts. Finally, there are some who argue that since leased assets may be firm‐specific, the risk of moral hazard may be great, resulting in a tradeoff of greater than one‐to‐one; that is, a dollar of a lease obligation uses more of debt capacity than a dollar of a debt obligation. A series of empirical tests are performed in this study on samples of approximately 600 firms, covering the years 1976 through 1981, with none of the three views supported by the results. Instead, the results indicate that leases and debt are complements; greater use of debt is associated with a greater use of leasing. This finding reappears consistently for each year, each definition of leverage ratios, and each approach to analysis. This complementary relationship persists even after refinements are made to the estimation technique.